Youth waqf in Islamic finance - Kamaruddin, Aisyah Farhah; Pawit, Mohamed Aslam; Mohd Idris, Ummul Athirah Fathihah; Mohammad Hatta, Mohammad Firdaus; Ismail, Zurina (Faculty of Business and Management, 2025)
The Youth Waqf project offers an innovative solution to Malaysia's affordable housing crisis by revitalizing underutilized waqf assets. With property prices rising and affordable housing dwindling, particularly for the B40 group earning less than RM2500 monthly, this initiative aims to develop waqf properties for charitable purposes. It encourages individuals and institutions to donate goods or property, ensuring affordable housing for those in need. The project, part of SkyLine Builders’ CSR program, allows low-income groups to rent homes at affordable rates, while society can contribute through cash waqf. The study, employing qualitative research through semistructured interviews with six key informants, identifies the main challenges and offers integrated solutions for waqf property growth, donor management, and community support. By emphasizing social impact, multi-stakeholder engagement, and the application of Waqf principles, the project seeks to reduce government housing costs, promote social equality, and generate significant social and economic benefits. Government support through streamlined regulation and effective waqf management is crucial for the project’s success. The Youth Waqf project could serve as a model for other developers, demonstrating how waqf can be leveraged to create sustainable, affordable housing solutions.